THE ABUNDANCES OF THE ELEMENTS OF THE MAGELLANIC CLOUDS - Chekhonadskikh, F. A. (Одеські астрономічні публікації, 2010)
The results of the spectroscopic researches of classical Chepheids of the Magellanic Clouds (MC) are presented in this paper. 21 spec tra for the Large Magellanic Cloud (LMC) and 10 for the Small Magellanic Cloud (SMC) were investigated. I obtained highly accurate values of effective temper atures (Teff ), of the logarithm of the surface gravity (log g), of the microturbulence velocity (Vt), of abun dances of elements for all of the objects. There is a good agreement with previous studies, some data were obtained for the first time.